Предмет: Алгебра,
автор: sonyalomovskay
замените звездочки такими одночленами чтобы получилось тождество: (3х-*)(*+5y)=6х^2+*+20y^2
Ответы
Автор ответа:
0
(3х-(-4у)) (2х+5у) =6х²+15ху+8ху+20у²=6х²+23ху+20у²
Автор ответа:
2
(3х-А)(В+5y)=6х^2+С+20y^2
3хВ=6х² В=2х
-А*5у=20у² -А=4у А=-4у.
(3х+4у)(2х+5y)=6х^2+15ху+8ху+20y^2
С=15ху+8ху=23ху
(3х+4у)(2х+5y)=6х^2+23ху+20y^2
3хВ=6х² В=2х
-А*5у=20у² -А=4у А=-4у.
(3х+4у)(2х+5y)=6х^2+15ху+8ху+20y^2
С=15ху+8ху=23ху
(3х+4у)(2х+5y)=6х^2+23ху+20y^2
Похожие вопросы
Предмет: Физика,
автор: Luynix
Предмет: Математика,
автор: Аноним
Предмет: Українська мова,
автор: mzdvvjpbmj
Предмет: Алгебра,
автор: umnik421